Targeting C-Type Lectin Receptors for Cancer Immunity - Yan, Huimin; Kamiya, Tomomori; Suabjakyong, Papawee; Tsuji, Noriko M. (Frontiers in Immunology, 2015)
C-type lectin receptors (CLRs) are a large family of soluble and trans-membrane pattern recognition receptors that are widely and primarily expressed on myeloid cells. CLRs are important for cell-cell communication and host defense against pathogens through the recognition of specific carbohydrate structures. Similar to a family of Toll-like receptors (TLRs), CLRs signaling are involved in the various steps for initiation of innate immune responses and promote secretion of soluble factors such as cytokines and interferons, Moreover, CLRs contribute to endocytosis and antigen-presentation, thereby fine-tune adaptive immune responses. In addition, there may also be a direct activation of acquired immunity. On the other hand, glycans, such as mannose structures, Lewis-type antigens or GalNAc are components of tumor antigens and ligate CLRs, leading to immunoregulation. Therefore agonists or antagonists of CLRs signaling are potential therapeutic reagents for cancer immunotherapy. We aim to overview the current knowledge of CLRs signaling and the application of their ligands on tumor-associating immune response.